Meta-Analysis of Risk Factors for Lower Extremity Amputation in Diabetes Mellitus Patients with Foot Ulcers - Septiani, Anissa Eka; Rahardjo, Setyo Sri; Prasetya, Hanung (Indonesian Journal of Medicine, 2020)
Background: Diabetic foot ulcer is a complication of diabetes mellitus which costs high, takes long wound care, increases mortality, morbidity and causes non-traumatic amputation. There are risk factors that are thought to be the cause of lower limb amputation in diabetic foot ulcers, namely peripheral artery disease, hypertension and gender. This study aims to estimate the influence of peripheral artery disease, hypertension and gender on the risk of lower limb amputation in diabetes mellitus patients with leg ulcers.Subjects and Method: Meta-analysis studies and systematic reviews were applied to this study using electronic databases of Pubmed, Scopus, Google Scholar, and Springer Link. The keywords to search for articles are as follows: "diabetic foot", "lower limb amputation", "lower extremity amputation", "risk factor", "predictor", "cohort", "retrospective", "adjusted odds ratio". Articles were collected using PRISMA diagrams, and analyzed using the Review Manager 5.3 application.Results: Meta-analysis of 9 cohort articles of diabetic foot ulcer patients with peripheral artery disease (aOR= 2.46; 95% CI= 1.70 - 3.55; p<0.01); Meta-analysis of 8 cohort articles, diabetic foot ulcer patients with hypertension (aOR= 1.05; 95% CI= 0.66 - 1.68; p= 0.83); Meta-analysis of 9 cohort articles of male diabetic foot ulcer patients (aOR= 1.60; 95% CI= 1.32 - 1.94; p<0.01); Peripheral artery disease, hypertension and male gender are risk factors that can increase the incidence of lower limb amputation.Conclusion: Peripheral artery disease, hypertension and male gender are risk factors that can increase the incidence of lower limb amputation.Keywords: Peripheral artery disease, diabetic foot ulcer, lower limb amputationCorrespondence: Anissa Eka Septiani. Masters Program in Public Health. Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java,. Email: sanissaeka@gmail.com. Mobile: 089514646458.Indonesian Journal of Medicine (2020), 05(04): 343-355https://doi.org/10.26911/theijmed.2020.05.04.10.